Demographic characteristics of elite Ethiopian endurance runners - Scott, R. A.; Georgiades, E.; Wilson, R. H.; Goodwin, W. H.; Wolde, B.; Pitsiladis, Y. P. (Medicine & Science in Sports & Exercise, 2003)
INTRODUCTION: The dominance of East-African athletes in distance running remains largely unexplained; proposed reasons include favorable genetic endowment and optimal environmental conditions. PURPOSE: To compare the demographics of elite Ethiopian athletes with the general Ethiopian population and assess the validity of reports linking running long distances to school with endurance success. METHODS: Questionnaires, administered to 114 members (male and female) of the Ethiopian national athletics team and 111 Ethiopian control subjects (C) obtained information on place of birth, language, distance and method of travel to school. Athletes were separated into three groups according to athletic discipline: marathon (M; N = 34); 5,000-10,000 m (5-10 km; N = 42); and other track and field athletes (TF; N = 38). Frequency differences between groups were assessed using contingency chi-square tests. RESULTS: Regional distributions of marathon athletes differed from controls (P < 0.001) and track and field athletes (P = 0.013), but not the 5- to 10-km athletes (P = 0.21). The 5- to 10-km athletes also differed from controls (P < 0.001). Marathon athletes exhibited excess from the regions of Arsi and Shewa (M: 73%; 5-10 km: 43%; TF: 29%; C: 15%). The language distribution of marathon athletes differed from all groups (P < 0.001), with a predominance of languages of Cushitic origin (M: 75%, 5-10 km: 52%, TF: 46%, C: 30%). A higher proportion of marathon athletes ran to school (M: 68%; 5-10 km: 31%; TF: 16%; C: 24%) and traveled greater distances. CONCLUSION: Elite endurance athletes are of a distinct environmental background in terms of geographical distribution, ethnicity, and also having generally traveled farther to school, often by running. These findings may reflect both environmental and genetic influences on athletic success in Ethiopian endurance athletes.